FORMATION AND MODIFICATION OF THE SHALLOW SUB-CONTINENTAL LITHOSPHERIC MANTLE: A REVIEW OF GEOCHEMICAL EVIDENCE FROM ULTRAMATIC XENOLITH SUITES AND TECTONICALLY EMPLACED ULTRAMAFIC MASSIFS OF WESTERN AND CENTRAL EUROPE - Downes H. (My University, 2001)
The petrology and geochemistry of shallow continental lithospheric mantle (SCLM) can be studied via (1) tectonically emplaced ultramafic massifs and (2) mantle xenoliths entrained in alkaline magmas. Data from these two separate sources are used to identify processes that have formed and modified the SCLM. In western and central Europe where the continental crust consolidated in Phanerozoic times, both sources of information are available for study. Rock types found in ultramafic massifs in Europe are generally similar to those found in ultramafic xenolith suites. The most frequent lithology is anhydrous spinel Iherzolite, grading towards harzburgite. Massifs reveal pyroxenite layering, harzburgite bands and cross-cutting and ultramafic dykes. The Phanerozoic European SCLM xenoliths and massifs show broad mineralogical and chemical similarities to Phanerozoic continental spinel peridotites world-wide. The main process that controls the geochemistry of the SCLM is depletion by removal of basaltic melt. Differences from this noem reflect significantly different processes in the SCLM, such as interaction with melts and fluids. Such processes probably gave rise to hornblendite veins and pyroxenite layers, although the latter have also been interpreted as recycled oceanic crust. Rare earth element data for whole-rock peridotites and their constituent clinopyroxenes show a variety of patterns, including light rare earth element (LREE) depletion as a result of removal of basaltic melt, LREE enrichment caused by metasomatism, and U-shaped REE patterns that are probably due to interaction with carbonatite melts. Extended mantle-normalized incompatible trace element patterns for whole rocks show enrichment in Rb and Ba in peridotites considered to have been subduction-metasomatized, whereas those considered to be carbonate-metasomatized have strong negative anomalies in Zr, Nb and Hf. Mantle amphiboles are strongly enriched in LREE when found in veins, but can be LREE depleted if they are interstitial. Radiogenic isotope ratios for xenoliths and massifs largely overlap, although the xenoliths show a significant clustering around a 'plume-component' identical to the Neogene alkaline magmatism of Europe. This component is lacking in the massifs, most of which were emplaced into the crust before the onset of Neogene plume activity. Infiltration of carbonatite melts is observed petrographically in some xenoliths and evidenced by low evidenced by low Ti/Eu ratios in bulk rocks, but is very rare. The effect of passage of hydrous fluids from subducting slabs is also seen in some suites and massifs, being exhibited mainly as unusual Sr and Pb isotope ratios, although enrichment in K, Rb and Ba, and the presence of modal phlogopite, may also point to to subduction-metasomatism.
Keywords: peridotites; xenoliths; orogenic massifs; Europe